Game related statistics discriminate national and foreign players according to playing position and team ability in the women`s basketball EuroLeague - Gasperi, L.; Conte, D.; Leicht, A.; Gómez-Ruano, M.-A. (International Journal of Environmental Research and Public Health, 2020)
The aim of the present study was to examine the differences in game-related statistics between national and foreign female basketball players in the Women`s EuroLeague, according to playing positions and team ability. The official box-scores of 112 games from the 2016-2017 season of the Women`s EuroLeague (FIBA) were examined. Players were categorised based upon country of nationality versus competition (i.e., foreign or national), playing positions (i.e., Guards, Forwards, Centers), and team ability (i.e., four groups using a cluster of k-means analysis according to the winning percentage of each team during the competition). A structural coefficient (SC) above |0.30| was used to identify the variables that best differentiated the national and foreign players. Results showed that foreign players had a better performance according to team ability and playing position for most of the performance indicators, with higher values for minutes played, percentage of successful 2-point field-goals, percentage of successful free-throws, and percentage of assists. Moreover, foreign players performed better in variables associated with offensive situations, while national players were prevailing with indicators associated with defensive actions. These results have highlighted the unique contributions of foreign and national players, based upon playing position and team ability, to team success in the Euroleague. This information will assist the recruitment process of national and foreign athletes for coaches to develop successful elite female basketball teams.